Assessment of cardiac function in mice lacking the mitochondrial calcium uniporter. (August 2015) - Holmström, Kira M.; Pan, Xin; Liu, Julia C.; Menazza, Sara; Liu, Jie; Nguyen, Tiffany T.; Pan, Haihui; Parks, Randi J.; Anderson, Stasia; Noguchi, Audrey; Springer, Danielle; Murphy, Elizabeth; et al.
Abstract: Mitochondrial calcium is thought to play an important role in the regulation of cardiac bioenergetics and function. The entry of calcium into the mitochondrial matrix requires that the divalent cation pass through the inner mitochondrial membrane via a specialized pore known as the mitochondrial calcium uniporter (MCU). Here, we use mice deficient of MCU expression to rigorously assess the role of mitochondrial calcium in cardiac function. Mitochondria isolated from MCU −/− mice have reduced matrix calcium levels, impaired calcium uptake and a defect in calcium-stimulated respiration. Nonetheless, we find that the absence of MCU expression does not affect basal cardiac function at either 12 or 20 months of age. Moreover, the physiological response of MCU −/− mice to isoproterenol challenge or transverse aortic constriction appears similar to control mice. Thus, while mitochondria derived from MCU −/− mice have markedly impaired mitochondrial calcium handling, the hearts of these animals surprisingly appear to function relatively normally under basal conditions and during stress. Highlights: MCU expression is required for rapid calcium uptake in cardiac mitochondria. Hearts lacking MCU have normal basal cardiac function. Deletion of MCU does not alter the response to transverse aortic constriction.